2021
DOI: 10.1186/s13722-021-00253-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial sustainability of payment models for office-based opioid treatment in outpatient clinics

Abstract: Background Office-Based Opioid Treatment (OBOT) is a delivery model which seeks to make medications for opioid use disorder (MOUD), particularly buprenorphine, widely available in general medical clinics and offices. Despite evidence supporting its effectiveness and cost-effectiveness, uptake of the OBOT model has been relatively slow. One important barrier to faster diffusion of OBOT may be the financial challenges facing clinics that could adopt it. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Keywords: opioid epidemic, primary health care, community health center, Office-based opioid treatment (OBOT) is a delivery model that seeks to make medications for opioid use disorder, including buprenorphine and extended-release naltrexone, available in general medical clinics and office settings (Hodgkin et al, 2021) and has been shown to improve patients' physical and mental health, provide similar treatment retention and rates of negative urine drug screens, and prevent HIV, hepatitis C, and other infectious diseases (Velander, 2018). Primary care OBOT offers whole-person care for people with substance use disorders by treating for comorbid mental health and psychiatric conditions, integrating harm reduction and recovery support, and coordinating access to the continuum of care.…”
Section: Public Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: opioid epidemic, primary health care, community health center, Office-based opioid treatment (OBOT) is a delivery model that seeks to make medications for opioid use disorder, including buprenorphine and extended-release naltrexone, available in general medical clinics and office settings (Hodgkin et al, 2021) and has been shown to improve patients' physical and mental health, provide similar treatment retention and rates of negative urine drug screens, and prevent HIV, hepatitis C, and other infectious diseases (Velander, 2018). Primary care OBOT offers whole-person care for people with substance use disorders by treating for comorbid mental health and psychiatric conditions, integrating harm reduction and recovery support, and coordinating access to the continuum of care.…”
Section: Public Significance Statementmentioning
confidence: 99%
“…Primary care OBOT offers whole-person care for people with substance use disorders by treating for comorbid mental health and psychiatric conditions, integrating harm reduction and recovery support, and coordinating access to the continuum of care. Cited barriers to providing OBOT include financial sustainability of payment models (Hodgkin et al, 2021), time, competing priorities, lack of collaborating specialists, and stigma (Louie et al, 2019; Russell et al, 2021). Additionally, primary care implementing OBOT to respond to the opioid epidemic during the COVID-19 pandemic simultaneously adapted their systems of care to the imperative public health interventions.…”
mentioning
confidence: 99%
“…Furthermore, virtual care implementation within organizations fluctuated due to staff turnover or equipment changes. Brief Report [107] [70, 75] Protocol [36] Review [108] QuADS: Quality Assessment with Diverse Studies…”
Section: Sivakumar Et Al [67]mentioning
confidence: 99%
“…New Jersey has numbered amongst the states with the highest opioid overdose rates with 30 deaths per 100,000 of the population [ 18 ] and in an effort to increase the number of buprenorphine providers, New Jersey has implemented a series of interventions to decrease barriers to buprenorphine prescribing. This includes eliminating medication prior authorizations for buprenorphine for all Medicaid plans as has been done in other states including Illinois and California, and implementing higher reimbursement for office-based addiction treatment as in Virginia and Massachusetts [ 19 , 20 ]. Financial incentives are often used to influence medical providers’ behaviors and a one-time incentive to obtain a DATA-2000 waiver has been piloted in Colorado, Pennsylvania and California [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%